2020
DOI: 10.38001/ijlsb.690295
|View full text |Cite
|
Sign up to set email alerts
|

The Important In Terms of Health of Flax (Linum usitatissimum L.)

Abstract: The flax is one of the oldest known cultivated plants of the World that benefited from seeds and fibers. It is an important nutrient because of the rich α-linolenic acid (ALA, omega-3 fatty acid), lignans, short chain polyunsaturated fatty acids, soluble and insoluble fibers, phytoestrogenic lignans (secoisolariciresinol diglycoside-SDG), waxy and mucilage compounds, protein and antioxidant compounds. In addition, the seed contains components effective in reducing cardiovascular disorders, diabetes, digestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 65 publications
0
4
0
1
Order By: Relevance
“…It is one of the oldest fiber plants in the world and is used in the production of environmental friendly durable composite materials [2,3] and paper [4] with its non-fiber wastagess. The seeds of flax plants are directly used as food in dietary products [5], as industrial oil [6], cooking oil, and the remaining residues containing rich nutritional contents are used as a food supplement [7] and as animal feed [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the oldest fiber plants in the world and is used in the production of environmental friendly durable composite materials [2,3] and paper [4] with its non-fiber wastagess. The seeds of flax plants are directly used as food in dietary products [5], as industrial oil [6], cooking oil, and the remaining residues containing rich nutritional contents are used as a food supplement [7] and as animal feed [8].…”
Section: Introductionmentioning
confidence: 99%
“…They are one of the oldest traditional annual cultivated crops in the world [11]. Several studies have indicated that flaxseed is a source of phytochemicals, with potential health benefits [12]. Based on these previous reports, flaxseed oil and fractions have important medicinal activities, including antioxidant, antiinflammatory, anticancer, antiviral, and bactericidal properties [13].…”
Section: Introductionmentioning
confidence: 99%
“…Omega yağ asitleri arasında, esansiyel olmaları yani vücutta sentezlenmeyip endojen olarak alınmaları gerektiğinden omega- [84,85]. Her iki bitki de gıda desteği olarak değerlendirilebilecek potansiyele sahip sağlık endüstrisi için önemli kaynaklardandır [83,85].…”
Section: Sonuçunclassified